Interactions between avian colonial social structure and disease dynamics - Wanelik, K (2015)
All wildlife populations harbour parasites. However, seabirds are likely to play a particularly important role in the maintenance and dispersal of infectious agents as a result of their colonial breeding habits. Seabird colonies are also known to be highly spatially structured, but little is known about the effects of this spatial structuring on seabird parasite dynamics. In this thesis, I use a tick-borne virus, Great Island virus (GIV), found in a large common guillemot (Uria aalge) colony bordering the North Sea as a model system to explore this relationship. I use a multidisciplinary approach, framed by a simple epidemiological model of the guillemot-tick-virus system. In Chapter 2, I describe a novel epidemiological model and parameterise it using the existing literature. The model suggests the importance of spatial structure within the guillemot colony, but also identifies a key missing parameter, the rate of virus transmission between pre-breeding and breeding areas. In Chapter 3, I go on to test the potential role of independent tick movement in driving transmission between these two areas, by quantifying the mobility of host-seeking seabird ticks, Ixodes uriae. I show the potential for ticks to walk ranges described anecdotally in the literature, in just a few minutes, but stress the importance of further experiments in the field./p> Chapter 4, I test the potential role of guillemot-mediated tick movement between pre-breeding and breeding areas. I show that pre-breeding guillemots spend a limited proportion of time ashore during daylight hours, which increases significantly as the season progresses and varies between individuals. A similar pattern is observed when considering how often they enter breeding areas when ashore; generally infrequently but varying spatiotemporally and between individuals. In Chapter 5, I apply finite mixture modelling techniques to improve existing estimates of age- and strain-specific GIV seroprevalence and force of infection in the guillemot colony. I also provide the first estimates of these parameters for eight strains, and highlight the importance of understanding strain-specific differences in GIV dynamics in future studies./p> Finally, I bring all four data chapters together in Chapter 6, by inputting my new parameter estimates (Chapters 3-5) into my existing model (Chapter 2). Taken together, my results suggest that GIV transmission within the guillemot colony may increase in the future as a result of declining breeding abundance and success, with more frequent or extreme disruption leading to a higher risk of infection within the colony. More generally, my results suggest that seabird colonies can be highly sensitive to changes in their spatial structure, and that endemic parasites have the potential to substantially impact, and hence to be an added threat to, their seabird hosts.